Pangye Surok 磻溪隨錄, Volume 9, Kyoson Chi che Sang 교선지제(敎選之制) 상(上) - Yu, Hyongwon (My University, 2013)
This chapter relates to village charters (hyangyak) and school regulations. Pan’gye Surok (磻溪隨錄) is Yu Hyŏng-wŏn’s (柳馨遠1622-1673) representative book on a reform for a Korean system of government. It consists of total of 26 volumes. In Pan’gye Surok, Yu extensively elaborates his ideas on reform for governmental organization. The main emphasis of the book is on the idea of land reform, through which the author gives well organized critiques and analysis for remodeling and redistributing wealth. The focus and suggestions for reform, however, also expand to social, military, and financial reforms. He also included a thorough examination of the many Chinese classical and historical texts as well as Korean primary sources and scholarship.
Keywords: Village Charter (Hyangyak), School regulations